Isolation and structure of an untriakontapeptide with opiate activity from camel pituitary glands. - Li, C H (1976)
The isolation of an untriakontapeptide from camel pituitary extracts has been described. Its structure has been determined and shown to be identical to the sequence of carboxyl-terminal 31 amino acids of ovine beta-lipotropin. The peptide possesses very low lipotropic activity but significant opiate activity.